2002
DOI: 10.1002/aqc.523
|View full text |Cite
|
Sign up to set email alerts
|

Use of tissue and sediment‐based threshold concentrations of polychlorinated biphenyls (PCBs) to protect juvenile salmonids listed under the US Endangered Species Act

Abstract: Under the Endangered Species Act, the National Marine Fisheries Service has authority to protect listed species from any adverse actions that may jeopardize the population's ability to recover and increase to sustainable levels. Listed salmon species in the northwest United States are known to travel through urban areas in their migration from river to ocean. Species such as the chinook salmon (Oncorhynchus tshawytscha) often spend several weeks in these urban estuaries where they can be highly exposed to urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 64 publications
(62 reference statements)
3
74
0
Order By: Relevance
“…For example, Meador et al (2002) proposed that a tissue concentration of 2.4 lg tPCBs/g lipid was a protective tissue quality guideline (TQG) for salmonids. This TQG describes the 10th percentile of a variety of adverse biological responses for nonembryonic salmonids (fry to adult) that was compiled from several research studies.…”
Section: Determining a Sediment Guideline Based On Bioaccumulationmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Meador et al (2002) proposed that a tissue concentration of 2.4 lg tPCBs/g lipid was a protective tissue quality guideline (TQG) for salmonids. This TQG describes the 10th percentile of a variety of adverse biological responses for nonembryonic salmonids (fry to adult) that was compiled from several research studies.…”
Section: Determining a Sediment Guideline Based On Bioaccumulationmentioning
confidence: 99%
“…Even though organismal lipid likely had little effect on the magnitude of bioaccumulation of PCBs for these fish (e.g., Stow et al 1996), we believe that tissue lipids will be a factor in determining the toxic response. As proposed elsewhere (Lassiter and Hallam 1990), the lipid content of tissue controls the proportional availability of accumulated hydrophobic toxicants and therefore the magnitude of the toxic response, which is a factor we considered when developing the tPCB TQG for salmonids (Meador et al 2002).…”
Section: Determining a Sediment Guideline Based On Bioaccumulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The absorption efficiency of PCBs by salmon has been estimated at 50-75% by Meador et al (2002) and confirmed in a field study (Jacobs et al, 2002). The absorption of PAHs by trout exposed through the diet to fluorene and three heteroaromatic compounds of similar physical-chemical properties to aNAs was shown to increase over time and can reach levels higher than 100% of daily dose, after 4 months exposure (Hellou et al, 2002b).…”
Section: Uptake From Feedmentioning
confidence: 95%